Pengaruh Penambahan Serbuk Kaca pada Stabilisasi Tanah Lempung Lunak di Daerah Kabupaten Karawang - Bayu Mustika Bhakti; Sri Wulandari (Rekayasa Sipil, 2023)
Problems that are often encountered in road construction are poor and unstable soil conditions. Soil conditions greatly affect the design process and the durability of the road. One thing that is usually done to improve soil properties is to add mixed materials to improve the soil properties. The purpose of this study was to determine the effect of adding Waste Glass Powder (WGP) on soil consistency and CBR value. The percentage of WGP used is 2.5%, 5%, 10%, 15% and 25%. The result is that the addition of WGP has significantly improved soil quality. The value of the plasticity index of the soil decreases, which means that the potential for swelling and shrinkage of the soil is also decreased. The CBR value of the soil also increased to 341.04%.